1990
DOI: 10.1203/00006450-199001000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Immunologic Characteristics of Healthy Children with Subnormal Serum Concentrations of IgG2

Abstract: ABSTRACT. To understand the relevance of subnormal serum concentrations of IgG2, we measured IgG2 in serum of 575 healthy children and identified 11 with concentrations >2 SD less than the mean for age. The levels of IgG2 present were similar to those found in symptomatic children with IgG2 subclass deficiency associated with antibody deficiency. The 11 children ranged in age from 1 to 14 y (mean = 5.7). Detailed clinical information was available on 10 of the 11 children and each was matched for age with two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0
2

Year Published

1991
1991
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(36 citation statements)
references
References 10 publications
2
32
0
2
Order By: Relevance
“…Two DS children, aged 8 and 10 years, had serum IgG2 levels below the 3rd percentile but showed an adequate increase of pneumococcal antibodies after immunization. Subnormal serum IgG2 levels do not necessarily reflect a functional immunodeficiency (21,22). An adequate response to pneumococcal antigens depends on an interaction between innate and adaptive immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Two DS children, aged 8 and 10 years, had serum IgG2 levels below the 3rd percentile but showed an adequate increase of pneumococcal antibodies after immunization. Subnormal serum IgG2 levels do not necessarily reflect a functional immunodeficiency (21,22). An adequate response to pneumococcal antigens depends on an interaction between innate and adaptive immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…Since IgG2 is the isotype that is primarily responsible for responses against polysaccharides, it was postulated that a deficiency of this subclass in children would predispose patients to infections with encapsulated bacteria. However, some studies identified children with low IgG2 levels in the healthy population without evidence of increased susceptibility to infections (127). Another study revealed a resolution of IgG2 deficiency in all children observed over a time period of 6 years (6).…”
Section: Igg Subclass Deficiencymentioning
confidence: 99%
“…Failure to produce antibodies in response to vaccination with bacterial proteins and polysaccharides is a better indication of susceptibility to infection. 9 The majority of children who failed to respond to vaccination with the capsular polysaccharide (polyribose phosphate) of HIB (HIB-PRP) had normal IgG 2 subclass concentrations. 21,22 Furthermore, IgG 1 is more e¤cient on a molar basis in activating e¡ector mechanisms like the classical pathway of the complement system and interaction with the relevant Fc receptors on phagocytic cells.…”
Section: Iggmentioning
confidence: 99%